2019
DOI: 10.1007/978-3-030-31332-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ultrasound Image Reconstruction Method on Breast Lesion Classification with Deep Learning

Abstract: Deep learning algorithms, especially convolutional neural networks, have become a methodology of choice in medical image analysis. However, recent studies in computer vision show that even a small modification of input image intensities may cause a deep learning model to classify the image differently. In medical imaging, the distribution of image intensities is related to applied image reconstruction algorithm. In this paper we investigate the impact of ultrasound image reconstruction method on breast lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Most of these DL architectures use a large data set; thus, it is required to apply an augmentation technique to avoid overfiting and to have better performance during classification. In this sense, the researchers mentioned in Table 6 [145,168,180,181] and Table 7 [35,49,62,66,152,182] the authors used transfer learning and ensemble methods, such as data augmentation, to improve the performance of the CNN network, reaching an 89.86% accuracy and 0.9578% AUC in DM, and an AUC of 0.68% on US images. Furthermore, Singh et al [165] showed that the results obtained with a GAN for breast tumor segmentation outperformed the UNet model, and the SegNet and ERFNet models yielded the worst segmentation results on US images.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these DL architectures use a large data set; thus, it is required to apply an augmentation technique to avoid overfiting and to have better performance during classification. In this sense, the researchers mentioned in Table 6 [145,168,180,181] and Table 7 [35,49,62,66,152,182] the authors used transfer learning and ensemble methods, such as data augmentation, to improve the performance of the CNN network, reaching an 89.86% accuracy and 0.9578% AUC in DM, and an AUC of 0.68% on US images. Furthermore, Singh et al [165] showed that the results obtained with a GAN for breast tumor segmentation outperformed the UNet model, and the SegNet and ERFNet models yielded the worst segmentation results on US images.…”
Section: Discussionmentioning
confidence: 99%
“…Michał Byra et al [15]studied the influence of ultrasound image reconstruction algorithm on the classification of breast lesions based on transfer learning. In order to minimize the degradation of classification performance caused by the reconstruction algorithm, they proposed a data expansion method and compared the three image reconstruction thresholds, which are 40dB, 50dB, and 60dB.…”
Section: Residual Networkmentioning
confidence: 99%
“…The reported metrics were as follows: accuracy was 90%; and sensitivity, specificity, and the area under the curve (AUC) were 86%, 96%, and 0.95, respectively. Byra et al 10 investigated an ultrasound image reconstruction method for use in breast lesion classification. The authors used the InceptionV3 model and the reported accuracy, sensitivity, specificity, and AUC were 78%, 77%, 78%, and 0.857, respectively.…”
Section: Introductionmentioning
confidence: 99%